Location of a Dexamethasone Implant at the Macula after Intravitreal Injection in a Silicone Oil-Filled Eye - Cenap Mahmut Esenulku; Murat Gunay (Case Reports in Ophthalmological Medicine)
Here, we report a case with cystoid macular edema (CME) due to central retinal vein occlusion (CRVO) presented with a dexamethasone implant (Ozurdex) trapped at the macula in her silicone oil- (SO-) filled eye after injection. No additional complications such as intraocular pressure (IOP) rise or retinal damage were observed. The CME was resolved during the follow-up period. At the last visit, 3 months following the injection, Ozurdex implant was found to be mostly dissolved without any additional ocular complications.